FACTORS INFLUENCING THE QUALITY OF DRINKING WATER FROM VENDING MACHINES IN THE INNER CITY OF BANGKOK - Akemi Kita; Tanasri Sihabut; Kraichat Tantrakarnapa (Public Health of Indonesia)
Objective: To investigate coliform contamination in drinking water from vending machines in the Rajvithi area of Bangkok.